P405 ALDOSTERONE AND INTERLEUKIN–6: IS IT A NEW ASSOCIATION IN COVID–19?. (18th May 2022) - Campana, P; Ranieri, A; Basile, C; Forzano, I; Perillo, E; Ciaramella, L; Follero, P; Tagliamonte, G; Sibilio, G
Abstract: Introduction: Several pieces of evidence have confirmed the interleukin–6 (IL–6) activity in the cytokine storm induced by COVID–19 pneumonia. Furthermore, the correlation between serum IL–6 levels and plasma aldosterone has been widely ascertained in patients with primary aldosteronism (PA). Hence, the highest levels of aldosterone may increase IL–6 in COVID–19 patients with PA. Case Presentation: We reported the clinical case of a 47–year–old woman with severe COVID–19 pneumonia complicated by Guillain–Barré Syndrome (GBS). At admission, the patient presented severe interstitial pneumonia complicated by hypoxemia and respiratory failure, which required mechanical ventilation. Blood tests revealed very high levels of IL–6 (serum IL–6: 402 pg / mL) and its soluble receptor (soluble IL–6 receptor> 1900 pg / mL). In addition, the patient was diagnosed with PA after accidental evidence of right adrenal adenoma, resistant arterial hypertension, severe hypokalemia, and elevated serum levels of aldosterone with a high aldosterone/renin ratio. Therefore, infusion therapy with spironolactone was administered with a rapid improvement of the clinical condition. Later she was diagnosed with acute motor and sensory axonal neuropathy and with the indication of motor rehabilitation. Conclusions: The higher aldosterone levels in PA could be associated with more severe forms of COVID–19, stimulating the production of IL–6 and its pro–inflammatory effects. Hence, the association between IL–6 and aldosterone may have a synergistic effect in the development of more severe complications such as GBS. The highest aldosterone levels and activity could be also identified in patients with COVID–19 pneumonia and secondary aldosteronism. More studies are needed to evaluate spironolactone therapy in COVID–19.